A SUMMARY OF CLOUD COMPUTING FOR DEVELOPING THE PROCESS OF E-LEARNING - Suresh, Dr. Koparthi; Prasad, Dr. RVVSV (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Online communication platforms are used to support e-learning, a kind of virtualized computing, and remote learning as a tool in the teaching-learning process. In the last two years, e-learning platforms have grown significantly. When the learning process is digitized, data mining for education information processing leverages information produced from internet databases to improve the educational learning paradigm for educational purposes. A potential platform for enabling e-learning systems is cloud computing. By offering a scalable solution for long-term transformation of computer resource use, it may be automatically changed. When engaging with large e-learning datasets, it is also easier to employ data mining methods in a distributed setting. The research offers an overview of cloud computing's present condition as well as illustrations of infrastructure that has been specifically created for a system like this. It also talks about e-learning techniques and cloud computing demonstrations.